PENINGKATAN MOTIVASI DAN HASIL BELAJAR DENGAN MEDIA “AKSELERASI INDONESIA” - Nur Kholis Huda (Dakwatuna: Jurnal Dakwah dan Komunikasi Islam, 2018)
The students’ low interest in learning Social science, especiallyon the changes of provinces in Indonesia, has an impact on their learning motivation which automatically makes the studying outcomes are not satisfying. This is experienced by class VI students of Jetis III Elementary school during 2016/2017 period. This article observes about the methods to increase learning motivation and student learning outcomes in Social Science particularly about the changes of Provinces in Indonesia by using media learning called "Indonesian Acceleration (I Love Learning Provinces in Indonesia). The method used to obtain data in the use of "Akselerasi Indonesia” or Indonesian Acceleration, learning media is Qualitative and quantitative research packaged in the classroom action research. The result of learning showsthe increase of students’ interest that can be proven bythe learning outcomes after using "Indonesian Acceleration" learning media.